The COVID - AGICT study: COVID–19 and advanced gastro-intestinal cancer surgical treatment. A multicentric Italian study on the SARS-CoV-2 pandemic impact on gastro-intestinal cancers surgical treatment during the 2020. Analysis of perioperative and short-term oncological outcomes. (April 2023) - Giuliani, Giuseppe; Guerra, Francesco; Messinese, Simona; Santelli, Francesco; Salvischiani, Lucia; Esposito, Sofia; Ferraro, Luca; Esposito, Alessandro; De Pastena, Matteo; Rega, Daniela; Delrio, Paolo; La Raja, Carlotta; et al.
Abstract: Background: This Italian multicentric retrospective study aimed to investigate the possible changes in outcomes of patients undergoing surgery for gastrointestinal cancers during the COVID-19 pandemic. Method: Our primary endpoint was to determine whether the pandemic scenario increased the rate of patients with colorectal, gastroesophageal, and pancreatic cancers resected at an advanced stage in 2020 compared to 2019. Considering different cancer staging systems, we divided tumors into early stages and advanced stages, using pathological outcomes. Furthermore, to assess the impact of the COVID-19 pandemic on surgical outcomes, perioperative data of both 2020 and 2019 were also examined. Results: Overall, a total of 8250 patients, 4370 (53%) and 3880 (47%) were surgically treated during 2019 and 2020 respectively, in 62 Italian surgical Units. In 2020, the rate of patients treated with an advanced pathological stage was not different compared to 2019 ( P  = 0.25). Nevertheless, the analysis of quarters revealed that in the second half of 2020 the rate of advanced cancer resected, tented to be higher compared with the same months of 2019 ( P  = 0.05). During the pandemic year 'Charlson Comorbidity Index score of cancer patients (5.38 ± 2.08 vs 5.28 ± 2.22, P  = 0.036), neoadjuvant treatments (23.9% vs. 19.5%, P  < 0.001), rate of urgent diagnosis (24.2% vs 20.3%, P  < 0.001), colorectal cancer urgent resection (9.4% vs. 7.37, P  < 0.001), and the rate of positive nodes on the total nodes resected per surgery increased significantly (7 vs 9% - 2.02 ± 4.21 vs 2.39 ± 5.23, P  < 0.001). Conclusions: Although the SARS-CoV-2 pandemic did not influence the pathological stage of colorectal, gastroesophageal, and pancreatic cancers at the time of surgery, our study revealed that the pandemic scenario negatively impacted on several perioperative and post-operative outcomes. Highlights: This multicentric Italian cohort study, including 8250 patients, demonstrated that the COVID-19 pandemic did not influence the stage of gastrointestinal cancer during the 2020.However, it showed an increased rate of cancer diagnosis following an urgent admission, of neoadjuvant treatment and of the mean number of positive lymph nodes during the 2020.